Tingkat konsumsi energi, karbohidrat, protein, lemak pada diet jantung lunak bubur dan diet jantung lunak tim dengan lama hari rawat inap pasien gagal jantung kongestif di Rumah Sakit Tk. II dr. Soepraoen Kota Malang - Azzahrah, Tiyan Tiara; Sutjiati, Endang; Mustafa, Annasari; Rahman, Nur (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2019)
Cardiovascular disease is the number one cause of death in the world. In Indonesia, heart and blood vessel disease continues to increase and will provide a burden of morbidity, disability and socio-economic burden to the families of sufferers, the community, and the country (MOH, 2013). Efforts to obtain healing from an illness, including cardiovascular disease, require proper treatment. Besides treatment, food is one of the supporting factors to accelerate the healing of diseases. The purpose of this study was to determine the level of consumption of energy, carbohydrates, proteins, fats in the porridge soft heart diet and the steamed soft heart diet with the length of stay of congestive heart failure patients in Rumah Sakit Tk. II Dr. Soepraoen, Malang. This research was conducted in June-July 2019. The results showed that the level of energy consumption, carbohydrates, protein, fat in the porridge soft heart diet and the steamed soft heart diet for the length of stay of congestive heart failure patients have similarities. On the porridge soft heart diet and the steamed soft heart diet both had long hospital stay which is 2 respondents, each of which had 5 days of hospital stay and short hospital stay which is 1 respondent, which had 4 days of hospital stay. Further research needs to be done regarding the level of consumption of energy, carbohydrates, proteins, fats on the porridge soft heart diet and the steamed soft heart diet with the length of stay of congestive heart failure patients with a larger sample size and different research methods.